Rayleigh-like waves in multilayered elastic media containing voids: Use of the Haskell matrix method. (April 2023) - Khurana, Aarti; Kaur, Savkirat; Tomar, SK
Using the Haskell matrix method, the dispersion relation of Rayleigh-like surface waves propagating through a multilayered elastic solid half-space is derived. Each layer as well as the half-space is assumed to have voids (pores) distributed evenly throughout. This dispersion relation is then reduced for a 2-layered model (single layer over a half-space) to study the characteristics of phase speed of Rayleigh-like wave. For a particular model, the numerical computations are performed to observe the effect of voids on the fundamental mode of Rayleigh-like waves for n = 2 and 3. For the 2-layered model, it is also shown that the particle motion remains elliptical but influenced by the presence of voids. In the absence of voids from the model, the dispersion relation earlier obtained by Haskell (1953) for the case n = 2 is recovered successfully.